ANALISIS KUALITAS SEMEN BEKU SAPI SIMMENTAL MENGGUNAKAN PENGENCER ANDROMED® DENGAN VARIASI WAKTU PRE FREEZING - Rizki Indah Pratiwi; Sri Suharyati; Madi Hartono (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
The goals of research was to know the effect of pre freezing time to the frozen semen quality ofSimmental and the best time of pre freezing that can preserve the frozen semen quality of Simmental.This study was conducted in Regional Technical Service Unit - Regional Artificial InseminationOffice Lampung, Terbanggi Besar District, Central Lampung Regency, Lampung Province on 7th –13th April 2014. The completely randomized design was used in this research with 5 treatments (5minutes; 6 minutes; 7 minutes; 8 minutes; 9 minutes) and 4 times of replication. The data wereanalyzed using analysis of variance and then continued with orthogonal polynomial test.The results showed that the time of pre freezing did not affect significantly (P> 0.05) on thepercentage of sperm motility and the percentage of life sperm after pre freezing, but the effect wassignificant (P <0.01) on the percentage of sperm motility and percentage of life sperm post thawing.Orthogonal polynomial test showed that the effect of pre- freezing time on the percentage of spermmotility and percentage of life sperm after thawing had linear pattern with each equation those were Y= -28,88+7,38X and Y = -24,97+8,09X. Pre freezing for 9 minutes was able to show the percentage ofsperm motility and percentage of life sperm after thawing better than the pre freezing for 5 − 8minutes.